PENERAPAN DESAIN VISUAL DAN OPTIMALISASI MEDIA DIGITAL SEBAGAI STRATEGI EFISIENSI NILAI UNTUK MENINGKATKAN DAYA SAING UMKM LELY GORDEN INTERIOR DI SIDOARJO - Moh. Ainul Fais; I Gusti Ayu Sri Deviyanti; Agus Rahmanto; Wiwik Prihartanti (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
Lely Gorden Interior, a small business in Sidoarjo, offers quality products but struggled to establish a clear visual identity and effectively use social media for promotion. As a result, its marketing efforts were less appealing and had limited reach. Through this Community Service Program (PkM), the team aimed to enhance the business image by introducing a new visual design and providing support with social media management. The program was carried out in a participatory manner, involving observation, interviews, SWOT analysis, visual identity design, mentoring for Instagram, TikTok, and Facebook, and joint evaluation. The results were encouraging: the business now has a consistent visual identity, comprising a logo, brochure, banner, business card, and product watermark, which enhances its professional appearance. Social media accounts that were once inactive are now better managed, reflected in the growth of followers, more active interactions, and positive consumer responses. These achievements demonstrate that simple yet consistent strategies can have a meaningful impact on improving the competitiveness of MSMEs. The program also emphasizes value-efficiency, showing how limited resources can be leveraged to produce effective, cost-efficient solutions.